2012
DOI: 10.1016/j.fertnstert.2012.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Preterm delivery and low birth weight in singleton pregnancies conceived by women with and without a history of infertility

Abstract: Objective To determine predictors of low birth weight (LBW) and preterm delivery (PTD) in singleton pregnancies conceived by women with and without a history of infertility. Design Retrospective cohort study. Setting Eleven infertility clinics in Northern California. Patients Three groups of women who carried singleton pregnancies to ≥ 20 weeks gestation: 542 infertile women who conceived after treatment, 441 infertile women who conceived spontaneously, and 1008 fertile women for comparison. Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Recent meta-analyses have revealed a higher rate of LBW in IVF singletons and twins, respectively, compared to natural conceptions (12, 13). Although some data suggests that singleton infants are also at increased risk of LBW, even at term (3, 4, 1419), other investigators have not observed such differences (2023). For instance, Isaksson et al reported that the incidence of LBW in IVF singletons was comparable to unassisted conceptions (24).…”
Section: Introductionmentioning
confidence: 96%
“…Recent meta-analyses have revealed a higher rate of LBW in IVF singletons and twins, respectively, compared to natural conceptions (12, 13). Although some data suggests that singleton infants are also at increased risk of LBW, even at term (3, 4, 1419), other investigators have not observed such differences (2023). For instance, Isaksson et al reported that the incidence of LBW in IVF singletons was comparable to unassisted conceptions (24).…”
Section: Introductionmentioning
confidence: 96%
“…One retrospective study of 11 infertility clinics in northern California compared three groups: infertile women who conceived after treatment (not limited to IVF), infertile women who conceived spontaneously, and fertile women. 7 Infertile women who conceived after treatment were at an increased odds of having a LBW infant, whereas infertile women who conceived spontaneously were comparable to fertile women. This study suggests that the fertility treatment is independently associated with LBW.…”
mentioning
confidence: 94%
“…This study suggests that the fertility treatment is independently associated with LBW. 7 More recently, attention has turned to the supraphysiologic estradiol levels resulting from ovarian stimulation during IVF as an etiology for adverse perinatal outcomes. Supraphysiologic estradiol levels can affect the peri-implantation maternal environment and possibly placental cell migration and invasion.…”
mentioning
confidence: 99%
“…Camarano et al (2) was a retrospective analysis nested within an existing large and validated Californian cohort of infertile women with external controls, although it would have been ideal to perform the entire study within the same cohort (4,5). More specifically, the investigators have reassured the editors-and, we hope, the readers-in regard to the issues of recall bias, the play of chance, and confounding; they used mediation analysis for further clarification and complied with the requirements of the Strobe Initiative on Observational Studies.…”
mentioning
confidence: 99%
“…The publication process for the manuscript submitted by Camarano et al (2) would be an example of the latter option. To the extent that up to 75% of perinatal mortality or morbidity is due to or associated with prematurity or low birth weight (LBW), their manuscript addressed a question of immense public health and reproductive importance.…”
mentioning
confidence: 99%